2012
DOI: 10.1063/1.3685899
|View full text |Cite
|
Sign up to set email alerts
|

Overtone-induced dissociation and isomerization dynamics of the hydroxymethyl radical (CH2OH and CD2OH). II. Velocity map imaging studies

Abstract: The dissociation of the hydroxymethyl radical, CH(2)OH, and its isotopolog, CD(2)OH, following excitation in the 4ν(1) region (OH stretch overtone, near 13,600 cm(-1)) was studied using sliced velocity map imaging. A new vibrational band near 13,660 cm(-1) arising from interaction with the antisymmetric CH stretch was discovered for CH(2)OH. In CD(2)OH dissociation, D atom products (correlated with CHDO) were detected, providing the first experimental evidence of isomerization in the CH(2)OH ↔ CH(3)O (CD(2)OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…1. As will be shown in Paper II, 18 the theoretical values for the CH 2 OH → CH 2 O + H, CD 2 OH → CD 2 O + H, and CD 2 OH → CHDO + D channels are in excellent agreement with the experimental ones. The CH 2 OH dissociation energy is also in excellent agreement with the calculations of Ref.…”
Section: A Pes Vibrational Energies and Key Energeticssupporting
confidence: 77%
See 1 more Smart Citation
“…1. As will be shown in Paper II, 18 the theoretical values for the CH 2 OH → CH 2 O + H, CD 2 OH → CD 2 O + H, and CD 2 OH → CHDO + D channels are in excellent agreement with the experimental ones. The CH 2 OH dissociation energy is also in excellent agreement with the calculations of Ref.…”
Section: A Pes Vibrational Energies and Key Energeticssupporting
confidence: 77%
“…In the paper following this one (Paper II, Ref. 18), new experimental results using velocity map imaging are presented, which give evidence for the participation of direct OH bond fission and isomerization in the overtone-induced predissociation of the hydroxymethyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…39,45,48 We have demonstrated vibrational resolution for H 2 CO and HCOH(D) cofragments generated in CH 2 OH(D) dissociation by measuring the kinetic energy distributions (KEDs) of H(D) products. 11,39 II. EXPERIMENTAL DETAILS The experimental arrangement for generating hyrodroxymethyl radicals in a molecular beam and detection of H(D) photofragments using SVMI was described in detail elsewhere, 39,45,48 and therefore only a brief description is given below.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and computational studies of ground and excited state photodissociation of CH 2 OH have been reported, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] as have studies of CH 3 CHOH. 17,18 Computational studies 10 complementing experimental studies 15 of the ground state photodissociation CH 2 OH(X 2 A) + hv → CH 2 O(X 1 A 1 ) + H have been reported. The computational work employed two high quality adiabatic potential energy surfaces (PESs), developed in that study 10 denoted KRBRK below.…”
Section: Introductionmentioning
confidence: 99%